2013
DOI: 10.1002/cne.23240
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and expression divergence of metabotropic glutamate receptor genes in the brain of zebrafish (Danio rerio)

Abstract: Glutamate, the most abundant excitatory neurotransmitter of the central nervous system, modulates synaptic transmission and neuronal excitability via metabotropic glutamate receptors (mGluRs). These receptors are essential components for diverse cognitive functions and they represent potential drug targets for the treatment of a number of neurological and psychiatric disorders. Here, we describe the phylogenetic relation and mRNA distribution of zebrafish mGluRs. In comparison to the eight mglurs present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 119 publications
4
39
1
1
Order By: Relevance
“…Consistent with this genome-wide analysis, also studies of protein families in zebrafish have shown that genes involved in neuronal function have often retained both 24 paralogues (Gesemann et al, 2010;Di Donato et al, 2013;Haug et al, 2013;.…”
Section: Over-retained Duplicates After Wgdssupporting
confidence: 55%
“…Consistent with this genome-wide analysis, also studies of protein families in zebrafish have shown that genes involved in neuronal function have often retained both 24 paralogues (Gesemann et al, 2010;Di Donato et al, 2013;Haug et al, 2013;.…”
Section: Over-retained Duplicates After Wgdssupporting
confidence: 55%
“…Intriguingly, the double inversion contains the metabotropic glutamate receptor genes mglur4 and mglur7 , which are broadly expressed in the zebrafish brain, including olfactory bulb and retina (Haug et al . ). mGlur7 plays an important role in hippocampus‐dependent spatial learning in mice (Goddyn et al .…”
Section: Resultsmentioning
confidence: 97%
“…In rodents, mGluRs have been implicated in various forms of the startle response, including regulation of paired-pulse inhibition by group II mGluRs, using pharmacological manipulation 50 . Recently, it has been shown that group II mGluRs are expressed across all main subdivisions of the zebrafish brain 51 . Indeed, we found that conventional agonism of group II mGluRs by L-CCG-1 lowers the zebrafish ASR threshold.…”
Section: Discussionmentioning
confidence: 99%